Dinamika landasan kewarganegaraan di indonesia: analisis integratif perspektif historis, yuridis, dan sosiologis - Azizurohim, Azizurohim (Maliki Interdisciplinary Journal, 2026)
Citizenship in the context of the modern state is not only interpreted as an administrative status, but also as a collective identity formed through the history, law, and social dynamics of society. This research aims to analyze the foundation of Indonesian citizenship through historical, juridical, and sociological perspectives and see the integrative linkages between the three. The research uses a qualitative approach with a literature study method through the analysis of academic literature, laws and regulations, and research results related to Indonesian citizenship. The results of the study show that historically Indonesian citizenship was born from the experience of colonialism, equal fate, and the struggle for independence which gave birth to a national identity based on Pancasila. Juridically, citizenship gains legitimacy through the 1945 Constitution of the Republic of Indonesia and Law Number 12 of 2006 which guarantees the equality of citizens' rights before the law. Meanwhile, sociologically, citizenship functions as an instrument of social integration that is able to unite ethnic, religious, and cultural diversity in Indonesia's national identity. This study concludes that the integration of historical, juridical and sociological foundations is important to build civic competence, strengthen national identity, and maintain national resilience in the midst of the challenges of globalization and social fragmentation.